The impact of emotional intelligence on life satisfaction among Chinese nurses: A chain mediating model - Qin, Yuan; Liu, Jiao; Wu, Dongmei (Frontiers in Psychology, 2023)
Nurses' life satisfaction exerts a positive impact on their professional careers, and it seriously affects their physical and mental health. Low life satisfaction has become a key factor in the global shortage of nurses. Emotional intelligence may protect nurses from negative emotions that can affect the care they provide, as well as their life satisfaction. In this study, 709 Chinese nurses were recruited as subjects to demonstrate the impact of emotional intelligence on life satisfaction as well as the role that self-efficacy and resilience play. Measures in the study include the demographic questionnaire, the Emotional Intelligence Scale, the General Self-Efficacy Scale, the Connor-Davidson Resilience Scale, and the Satisfaction with Life Scale. SPSS 26.0 and Process V3.3 were used for statistical processing. Under the premise of controlling variables like age, educational level, working years, nursing title, and marital status, the results indicated that emotional intelligence was positively associated with life satisfaction among Chinese nurses, and self-efficacy and resilience were partially mediated between these two variables. Furthermore, the continuous intermediary effect of self-efficacy and resilience between these two variables has also been demonstrated.